Do We Need the Environment to Explain Operant Behavior? - Overskeid, Geir (Frontiers in Psychology, 2018)
By way of operant conditioning, human behavior is continuously shaped and maintained by its consequences – and understanding this process is important to most fields of psychology and neuroscience. The role of the learning organism’s environment has long been contentious, however. Much relevant research is being done by people identifying with the Skinnerian tradition, who tend to agree that the causes of behavior can be found exclusively in the environment. The meaning of this proposition is not clear, however. Some authors say the environment is outside the body, others claim it is also inside it. Among those who say the environment is outside the body, many are of the opinion that events inside the body and hence (in their view) not in the environment can also cause behavior, though they claim that events inside the body cannot be causes in the same sense as events taking place outside it. This is confusing, and the present paper argues that the “environment” may neither be a useful nor a necessary concept in the analysis of behavior. Moreover, abolishing the concept could clear the way for a reintegration of Skinnerian psychology into the mainstream.